Polymer Gels Perspectives and Applications - Thakur, Vijay Kumar; Thakur, Manju Kumari; Voicu, Stefan Ioan (Gels Horizons: From Science to Smart Materials, 2018)
This book summarizes the recent advances in the science and engineering of polymer-gel-based materials in different ﬁelds. It also discusses the extensive research developments for the next generation of smart materials. It takes an in-depth look at the current perspectives and market opportunities while pointing to new possibilities and applications. The book addresses important topics such as stimuli responsive polymeric nanoparticles for cancer therapy; polymer gel containing metallic materials; chemotherapeutic applications in oncology; conducting polymer-based gels and their applications in biological sensors; imprinted polymeric gels for pharmaceutical and biomedical purposes; applications of biopolymeric gels in the agricultural sector; application of polymer gels and their nanocomposites in electrochemistry; smart polyelectrolyte gels as a platform for biomedical applications; agro-based polymer gels and their application in purification of industrial water wastes; polymer gel composites for bio-applications. It will be of interest to researchers working in both industry and academia.